2006
DOI: 10.1614/wt-04-132r2.1
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Glyphosate Application on Control of Silverleaf Nightshade and Glyphosate-Resistant Cotton Yield

Abstract: A 3-yr dryland study was initiated in 1999 at Munday, TX, on an Altus fine sandy loam to determine the most appropriate cotton growth stage or stages at which to apply glyphosate. The objectives were: (1) to evaluate control of silverleaf nightshade in the cotton and (2) to determine the effect on yield. Treatments were: (1) control (C; two cultivations), (2) early glyphosate at the four-leaf stage (E), (3) early glyphosate followed by a midseason application 21 d later (E+M), (4) two cultivations plus late gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…For example, the allelopathic mechanisms can be incorporated in agro-ecosystems for weed control through several ways such as the inclusion of allelopathic crops in crop rotations, the use of their residues for cover cropping, or by selection of the most active allelochemicals to be used as bioherbicides ). In the case of S. elaeagnifolium, it may also be combined with current chemical control methods (Cambardella & Elliott 1992, Choudhary & Bordovsky 2006, Gitsopoulos et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the allelopathic mechanisms can be incorporated in agro-ecosystems for weed control through several ways such as the inclusion of allelopathic crops in crop rotations, the use of their residues for cover cropping, or by selection of the most active allelochemicals to be used as bioherbicides ). In the case of S. elaeagnifolium, it may also be combined with current chemical control methods (Cambardella & Elliott 1992, Choudhary & Bordovsky 2006, Gitsopoulos et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Applying glyphosate at the end of summer can enhance rootbank control, because during this period the carbohydrates and the nutrients move into the root system and this contributes to increased movement of the herbicide towards roots (Kidston et al, 2007). However, Choudhary and Bordovsky (2006) found that applying glyphosate late in the season was not effective on silverleaf nightshade. Previous research has provided variable results related to the most appropriate growth stage of silverleaf nightshade to apply glyphosate (Feuerherdt, 2010).…”
Section: Resultsmentioning
confidence: 97%
“…It can be used in fruit orchards, vineyards, and other row-seeded crops with directed-spray applications. It has been reported to efficiently control silverleaf nightshade in glyphosateresistant cotton (Choudhary and Bordovsky, 2006;Joy et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Some key attributes favor its growth and colonization potential in new regions; namely: (i) high seed production potential with up to 60 berries per plant accounting up to 120 seeds per berry, 21 (ii) rhizome fragmentation after tillage may generate multiple new stems, 29 (iii) extended root system, that makes conventional tillage insufficient, 29 (iv) low efficacy of systemic herbicides, 30 (v) tolerance to various biotic and abiotic stresses, 31 and (vi) high adaptability dynamics to various soil and environmental conditions. Solanum elaeagnifolium has been reported to compete with wheat (Triticum aestivum L.), maize (Zea mays L.), cotton (Gossypium hirsutum L.), sorghum (Sorghum bicolor L.), pepper (Capsicum annuum L.), peanut (Arachis hypogaea L.), and alfalfa (Medicago sativa L.), 22,25,32 while it has been also observed in olives and citrus orchards. It is present in forest edges but not inside a forest environment.…”
Section: Integrated Management Of Important Ips: Two Case-studiesmentioning
confidence: 99%